SASARAN DAN TOPIK PEMBAHASAN SELF DISCLOSURE MAHASISWA - Chalidaziah, Wan (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2019)
The background of this research is the low self-disclosure of students in the College of Islamic Guidance and Counseling X. The purpose of this research are to explain of self-disclosure in Islamic Guidance and Counseling students with a review of the target and discussion topics. The Method was descriptive quantitative research.  The research population was the students of guidance and counseling. The sample counsists of 122 students with Random Sampling technique. The research instrument used a Self Disclosure Scale with 54 statement items (r = 0.91029). The Data analyzed by using descriptive. The result of determined that most student only give their information only in general, and some students have not been able to share their information with others. The results of this study also indicate that the significant person in self disclosure is the mother and the most open discussion topic on the topic of interests and tastes. Researchers suggest further action research in the form of training to improve self-disclosure given the importance of self-disclosure skills in student guidance and counseling.